De novo missense mutation in MYT1l leading to autosomal dominant intellectual disability 39 and autism spectrum disorder: a case report - Wang, Xin; Lin, Shuangzhu; Chen, Yang; Qi, Yangfan; Sun, Xiaoyu; Wang, Wanqi; Jiang, Kai (Frontiers in Pediatrics, 2025)
BackgroundAutosomal dominant intellectual disability type 39 (MRD39; OMIM # 616521) is caused by heterozygous mutation in the MYT1l gene on chromosome 2p25.3. The MYTL1 encoded protein belongs to a novel class of cystein-cystein-histidine-cystein zinc finger proteins that function in the developing mammalian central nervous system.Case summaryWe report a 1-year-6-month-old girl presenting with global developmental delay (GDD) and autistic behaviors, demonstrating inability to stand independently, crawling mobility, poor response to name calling, and impaired joint attention. Initial developmental assessments yielded a Griffiths Mental Development Scale score of 57 and an ADOS-2 score of 11. Following 20 months of systematic rehabilitative training, the patient achieved independent ambulation, could follow simple commands, and produced phrases under 10 words, though suboptimal response to name calling and joint attention persisted. Re-evaluation showed a Griffiths score of 59 and an ADOS-2 score of 10. Whole-exome sequencing identified a de novo heterozygous missense variant in the MYT1l gene [c.1695G > T; p.(Arg565Ser)]. According to the American College of Medical Genetics and Genomics (ACMG) guidelines, this variant was classified as Likely Pathogenic based on criteria PM6 (de novo status) and PM2 (absence in population databases). Based on the concordant genotype and phenotype, the patient was diagnosed with MYT1l-related neurodevelopmental disorder (MRD39).ConclusionWe report a case of MYT1l-related disorder presenting with global developmental delay and features of autism spectrum disorder, associated with the previously documented but functionally uncharacterized c.1695G > T (p.Arg565Ser) variant. This case provides valuable clinical evidence supporting the pathogenicity of this variant and contributes to a deeper understanding of the phenotypic spectrum of MYT1l-related conditions.